Olfactory impairment in the rotenone model of Parkinson’s disease is associated with bulbar dopaminergic D2 activity after REM sleep deprivation - Rodrigues, Lais S. (Front Cell Neurosci, 2014)
Olfactory and rapid eye movement (REM) sleep deficits are commonly found in untreated subjects with a recent diagnosis of Parkinson’s disease (PD). Additionally, different studies report declines in olfactory performance during a short period of sleep deprivation. Mechanisms underlying these clinical manifestations are poorly understood, and impairment of dopamine (DA) neurotransmission in the olfactory bulb and the nigrostriatal pathway may have important roles in olfaction and REM sleep disturbances. Therefore, we hypothesized that modulation of the dopaminergic D2 receptors in the olfactory bulb could provide a more comprehensive understanding of the olfactory deficits in PD and REM sleep deprivation (REMSD). We decided to investigate the olfactory, neurochemical, and histological alterations generated through the administration of piribedil (a selective D2 agonist) or raclopride (a selective D2 antagonist) within the glomerular layer of the olfactory bulb, in rats subjected to intranigral rotenone and REMSD. Our findings provide evidence of the occurrence of a negative correlation (r = −0.52, P = 0.04) between the number of periglomerular TH-ir neurons and the bulbar levels of DA in the rotenone, but not sham, groups. A significant positive correlation (r = 0.34, P = 0.03) was observed between nigrostriatal DA levels and olfactory discrimination index (DI) for the sham groups, indicating that increased DA levels in the substantia nigra pars compacta (SNpc) are associated with enhanced olfactory discrimination performance. Also, increased levels in bulbar and striatal DA were induced by piribedil in the rotenone control and rotenone REMSD groups, consistent with reductions in the DI. The present evidence reinforce the idea that DA produced by periglomerular neurons, particularly the bulbar dopaminergic D2 receptors, is an essential participant in olfactory discrimination processes, as the SNpc, and the striatum.